Anaplasmosis in Pennsylvania: Clinical Features, Diagnosis, and Outcomes of Patients Diagnosed With Anaplasma phagocytophilum Infection at Hershey Medical Center From 2008 to 2021. (12th April 2023) - Ingram, David; Joseph, Betsy; Hawkins, Stephanie; Spain, James
Abstract: Anaplasmosis is an emerging infection in the United States and in particular, Pennsylvania. We highlight the abrupt rise in cases of anaplasmosis in the past decade in the state of Pennsylvania with the hope of increasing clinician awareness. We identified a cohort of 61 patients diagnosed with anaplasmosis at our institution as well as cases reported to the Department of Health. From our review, we identified not only an increase in cases over time but what appears to be an expansion further into central and western Pennsylvania over time.